The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/1528-3577.04103
|View full text |Cite
|
Sign up to set email alerts
|

U.S.-Africa Virtual Collaboration in Globalization Studies: Success Factors for Complex, Cross-National Learning Teams

Abstract: This case study highlights findings from the first two years of a crossinstitutional and cross-national effort to link university students in South Africa with university students in the United States via a graduate seminar on globalization and the information society. The seminar is taught using synchronous and asynchronous web-based tools, providing students with the opportunity to participate in complex, cross-national learning teams. These Global Syndicates represent important stakeholders in globalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 19 publications
5
26
2
Order By: Relevance
“…Interestingly, Jarvenpaa and Leidner's ( 1999 ) fi ndings showed that culture is an insignifi cant factor in predicting the perceived level of trust in GVTs. They allege that, in an electronic communication environment, culture is less signifi cant, whereas our research argues the opposite view (Amant, 2002 ;Cogburn & Levinson, 2003 ;Mohd Yusof & Zakaria, 2012 ;Zakaria, 2006 ). Hall ( 1976 ) argued that people who demonstrate high context communication behaviors rely primarily on the nonverbal aspects of messages and the contextual value of information.…”
Section: The Impact Of Culture On Building Swift Trust In Global Virtcontrasting
confidence: 62%
“…Interestingly, Jarvenpaa and Leidner's ( 1999 ) fi ndings showed that culture is an insignifi cant factor in predicting the perceived level of trust in GVTs. They allege that, in an electronic communication environment, culture is less signifi cant, whereas our research argues the opposite view (Amant, 2002 ;Cogburn & Levinson, 2003 ;Mohd Yusof & Zakaria, 2012 ;Zakaria, 2006 ). Hall ( 1976 ) argued that people who demonstrate high context communication behaviors rely primarily on the nonverbal aspects of messages and the contextual value of information.…”
Section: The Impact Of Culture On Building Swift Trust In Global Virtcontrasting
confidence: 62%
“…In fact, multi-institutional partnerships and international academic collaboration with African public universities were not new, and in recent decades, overall, cross-national collaborations with U.S. Universities were on the rise (Cogburn & Levinson, 2003;Witt, 2010). Some scholars speculate further that the worldwide expansion of international knowledge and linkages was spurred as recently as 2003 by the altered conditions across the globe resulting from expanded globalization and the sense of heightened international conflict after 9/11, followed by the Iraq war (Wiley & Root, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2 Such strategies can immerse students into environments and involve them with course materials that traditional techniques like reading and lecturing cannot (Caruson 2005, 305). As many point out, there are multiple ways to engage students with active learning strategies: e.g., study abroad trips (Thies 2005;Bowman and Jennings 2005); Kolb's (1984) experimental learning model; web-based exercises (Cogburn and Levinson 2003); classroom simulations (Smith and Boyer 1996); and even film (Kuzma and Haney 2001). Our focus is on the use of simulations in the classroom and their effectiveness for encouraging and facilitating a student's ability to learn.…”
Section: Introductionmentioning
confidence: 99%